Regenerative Endodontics: Barriers and Strategies for Clinical Translation - Kim, Sahng G. (2012)
Despite a great deal of enthusiasm and effort, regenerative endodontics has encountered substantial challenges towards clinical translation. Recent adoption by the American Dental Association (ADA) of evoked pulp bleeding in immature permanent teeth is an important step for regenerative endodontics. However, there is no regenerative therapy for the majority of endodontic diseases. Simple recapitulation of cell therapy and tissue engineering strategies that are under development for other organ systems has not led to clinical translation in regeneration endodontics. Dental pulp stem cells may appear to be a priori choice for dental pulp regeneration. However, dental pulp stem cells may not be available in a patient who is in need of pulp regeneration. Even if dental pulp stem cells are available autologously or perhaps allogeneically, one must address a multitude of scientific, regulatory and commercialization barriers, and unless these issues are resolved, transplantation of dental pulp stem cells will remain a scientific exercise, rather than a clinical reality. Recent work using novel biomaterial scaffolds and growth factors that orchestrate the homing of host endogenous cells represents a departure from traditional cell transplantation approaches and may accelerate clinical translation. Given the functions and scale of dental pulp and dentin, regenerative endodontics is poised to become one of the early biological solutions in regenerative dental medicine.